Factors associated with employment outcome after critical illness: Systematic review, meta‐analysis, and meta‐regression. (19th November 2020) - Su, Han; Dreesmann, Nathan J.; Hough, Catherine L.; Bridges, Elizabeth; Thompson, Hilaire J.
Abstract: Aims: To synthesize data on prevalence and risk factors for return to work (RTW) in ICU survivors. Design: Systematic review and meta‐analysis. Data sources: PUBMED, CINAHL, EMBASE and PsycINFO databases were searched from 2000–Feb 2020. Review methods: Peer‐reviewed articles that included adult ICU survivors and employment outcomes. Two investigators independently reviewed articles following the PRISMA protocol. Pooled prevalence for RTW was calculated. Meta‐regression analyses were performed to assess the association between disability policies, temporal factors and RTW following ICU. Results: Twenty‐eight studies ( N = 8, 168) met the inclusion criteria. All studies were scored as 'low risk of bias'. Using meta‐analysis, the proportion (95% CI) of RTW following ICU was 29% (0.20, 0.42), 59% (0.50, 0.70), 56% (0.50, 0.62), 63% (0.54, 0.72), 58% (0.37, 0.91), 58% (0.42, 0.81), and 44% (0.25, 0.76) at 3, 4–6, 7–12, 13–24, 25–36, 37–48, and 49–60 months, respectively. Time and disability policy support are factors associated with the proportion of ICU survivors who RTW. Through meta‐regression, there is a 20% increase (95% CI: 0.06, 0.33) in the proportion of individuals who RTW per year. However, the average rate of increase slows by 4% (−0.07, −0.1) per year. In countries with high support policies, the proportion of RTW is 32% higher compared with countries with low support policies (0.08, 0.24). However, as subsequent years pass, the additional proportion of individuals RTW in high support countries declines (β = −0.06, CI: −0.1, −0.02). Conclusions: Unemployment is common in ICU survivors. Countries with policies that give higher support for disabled workers have a higher RTW proportion to 3 years following ICU admission. However, from 3–5 years, there is a shift to countries with lower support policies having better employment outcomes. Impact: Health care policies have an impact on RTW rate in survivors of ICU. Healthcare providers, including nurses, can function as public advocates to facilitate policy change. 摘要: 目的: 综合汇总ICU康复者复工(RTW)的患病率和风险因素 设计: 系统评估和荟萃分析。 数据来源: 检索PUBMED、CINAHL、EMBASE和PsycINFO数据库自2000年至2020年2月期间的数据。 评估方法: 同行评审文章包含成年人ICU康复者和就业结果。两位研究员各自按照PRISMA方案对文章进行了评估。计算了复工后的合并就业率。采用了荟萃回归分析, 评估残疾政策、暂时性因素以及ICU后复工之间的关系。 结果: 28份研究( N = 8, 168)符合纳入标准。其中, 所有研究都被评为'低偏见风险'。通过荟萃分析, ICU复工率(95%CI)在3个月时为29% (0.20和0.42), 4‐6个月时为59%(0.50和0.70), 7‐12个月时为56%(0.50和0.62), 13‐24个月时为63%(0.54和0.72)、25‐36个月时为58%(0.37和0.91)、37‐48个月时为58%(0.42和0.81)以及49–60 个月时为44%(0.25和0.76)。时间和残疾政策支持是与ICU复工幸存者的比例有关的因素。通过荟萃回归, 复工患者的比率每年上升20%(95% CI: 0.06和0.33)。然而, 平均增长率每年下降4%(−0.07和 −0.1)。政策支持力度大的国家, 其复工比率比政策支持力度小的国家高32%(0.08和0.24)。然而, 在之后的几年中, 政策支持力度大的国家, 其额外个人复工比率有所降低(β = −0.060和CI: −0.1和−0.02)。 结论: ICU康复者失业是非常常见的事情。在为残疾工人提供较高支持政策的国家中, ICU住院3年后的复工比率较高。然而就3到5年以及之后的复工率而言, 反而是政策支持力度低的国家就业情况比较可观。 影响: 医保政策对ICU康复者的复工率有一定影响。包括护士在内的医保提供者可作为公共提倡者, 从而促进政策变更。